(3GdQSGFd GdWHjI GdSfLQjIs - (3HTQ Hf jYbhH Hf ESMGb GdSfLQj GdeJWHH, CHj Sgds ((3eMeO Hf CHj HcQ Hf eMeO GdhQGb s)
(3ChdgG (B:s
(3GdMeO ddg GdeHJOY ai GHJOGFg bGd CHh Sgd HTQ Hf jYbhH Hf ESMGb GdSfLQi , CeG HYO (B: (3aEf GdCejQ CHG CMeO Nda s
(3BNQgG (B:s
(3CUd MeGU jQi GdGSJWdGY MjK GdQUGU Je GdebGdI GdQGHYI MjK GdQSGdI GdWHjI GdSfLQjI s
(3jTJed Ydi CQHY ebGdGJ cd ebGdI eagQSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B90 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs